Determination of Anti-Xa Inhibitor Plasma Concentrations Using a Universal Edoxaban Calibrator - Annika Burger; Jan-Dirk Studt; Adriana Mendez; Lorenzo Alberio; Pierre Fontana; Walter A. Wuillemin; Adrian Schmidt; Lukas Graf; Bernhard Gerber; Cédric Bovet; Thomas C. Sauter; Nikolaus B. Binder; et al. (Diagnostics, 2023)
A universal calibrator for the determination of all anti-Xa inhibitors would support laboratory processes. We aimed to test the clinical performance of an anti-Xa assay utilizing a universal edoxaban calibrator to determine clinically relevant concentrations of all anti-Xa inhibitors. Following a pilot study, we enrolled 553 consecutive patients taking rivaroxaban, edoxaban, or apixaban from nine study centers in a prospective cross-sectional study. The Technochrom® anti-Xa assay was conducted using the Technoview® edoxaban calibrator. Using ultra-high-performance liquid chromatography-tandem mass spectrometry (LC-MS/MS), anti-Xa inhibitor drug concentrations were determined. Sensitivities and specificities to detect three clinically relevant drug concentrations (30 µgL−1, 50 µgL−1, 100 µgL−1) were determined. Overall, 300 patients treated with rivaroxaban, 221 with apixaban, and 32 with edoxaban were included. The overall correlation coefficient (rs) was 0.95 (95% CI 0.94, 0.96). An area under the receiver operating characteristic curve of 0.96 for 30 µgL−1, 0.98 for 50 µgL−1, and 0.99 for 100 µgL−1 was found. The sensitivities were 92.3% (95% CI 89.2, 94.6), 92.7% (89.4, 95.1), and 94.8% (91.1, 97.0), respectively (specificities 82.2%, 93.7%, and 94.4%). In conclusion, the clinical performance of a universal, edoxaban-calibrated anti-Xa assay was solid and most drug concentrations were predicted correctly.